Case Report: Eculizumab in highly active myasthenia gravis complicated by severe infections - Deng, Yufei; Luo, Haocheng; Zhang, Chaoyue; Yang, Li; Wang, Shuangshuang; Zhang, Xuxiang; Yan, Xianni; Yang, Xiaojun; Jiang, Qilong (Frontiers in Immunology, 2025)
Highly active myasthenia gravis refers to a subset of refractory patients who exhibit recurrent exacerbations and crises. Eculizumab, a complement C5 inhibitor, has shown its efficacy and safety for patients with anti-acetylcholine receptor antibody-positive(AchR +)refractory generalized myasthenia gravis(gMG) in the REGAIN trial. However, the efficacy and safety of eculizumab in treating MG patients with severe infections have not yet been supported by clinical evidence. This is a case series reporting four patients with highly active myasthenia gravis complicated by severe infections. Changes in Myasthenia Gravis-Activities of Daily Living (MG-ADL) and Quantitative Myasthenia Gravis (QMG) scores were recorded before and after 12 injections of eculizumab to assess efficacy. Pathogen characteristics of infections were summarized using bacterial culture and next-generation sequencing (NGS) results, presented as a heatmap to illustrate pathogen species and abundance. Inflammatory markers, including Procalcitonin (PCT), C-Reactive Protein (CRP), neutrophil count, and total lymphocyte count, were monitored to evaluate the safety. Treatment regimens were retrospectively analyzed to further assess clinical outcomes and safety. The baseline ADL data for the four patients was 22 ± 2.31 (Mean ± SD), and the baseline QMG data was 30.5 ± 8.23. After 12 injections of eculizumab treatment, the scores decreased to ADL 4.75 ± 3.3 and QMG 14 ± 3.37. During the treatment, no apparent worsening of infections related to Eculizumab was noted. Three patients successfully had their tracheostomy tubes removed, and none of the four patients experienced further myasthenic crises. Eculizumab demonstrated clinical improvement in this series, and the treatment was well-tolerated. This case series addresses the need for data on complement inhibitors in highly active myasthenia gravis patients with severe infections, provides clinical reference support for the expanded application of eculizumab.